PELATIHAN MANAJEMEN EMOSI DAN KECENDERUNGAN SIMTOM DEPRESI PADA REMAJA DI PANTI ASUHAN - Erik Erik; Fellianti Muzdalifah (Journal of Research and Measurement in Psychology, 2013)
The purpose of this study was to determine the effectiveness of emotion management training toward depression tendency symptoms on adolescents at Panti Sosial Asuhan Anak Putra Utama 4 Jakarta. The study was conducted from March to December 2012 were conducted with adolescents at Panti Sosial Asuhan Anak Putra Utama 4, Jakarta. This study used pre-experimental research methods with a research one-group pretest-posttest design. Subjects numbered 8 participants. The collection uses BDI (Beck Depression Inventory) scale. Statistical analysis using the Wilcoxon test. Based on the results of data obtained z = -1.474, p = 0.141 (p > 0.05) (not significant), means that the emotion management training is not effective toward depression tendency symptoms on adolescents at Panti Sosial Asuhan Anak Putra Utama 4 Jakarta before treatment (pretest) and after treatment (posttest). This result showed the emotion management training is not effective toward depression tendency symptoms on adolescents at Panti Sosial Asuhan Anak Putra Utama 4 Jakarta on adolescents at Panti Sosial Asuhan Anak Putra Utama 4 Jakarta.